Photocatalytic hydrogen evolution of 1-tetralones to α-naphthols by continuous-flow technology. Issue 13 (18th June 2019) - He, Xu; Zheng, Yi-Wen; Lei, Tao; Liu, Wen-Qiang; Chen, Bin; Feng, Ke; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : A photoredox platform for the dehydrogenation of 1-tetralones to α-naphthols is disclosed. Further improvement is achieved using the continuous-flow approach. Abstract : Taking advantage of the synergy between photocatalysis and cobaloxime catalysis, the keto–enol radical cation of 1-tetralones becomes compatible with the transformation of various 1-tetralones into α-naphthols and H2 by virtue of the continuous-flow approach without any sacrificial oxidants under unusually mild conditions.